Analysis of the Use of Remittance Patterns of Indonesian Migrant Workers from Jago Village, Central Lombok Regency - Algifari Rozak Firdaus; Siti Maryam; Helmi Fuadi; Kevin Hewison; Hazera-Tun-Nessa (Economy and Finance Enthusiastic, 2023)
The migration issue begins with the occurrence of development inequality, which results in high unemployment rates. One of the factors contributing to high unemployment is the limited capacity of a country's economic growth to create new job opportunities, while the number of job seekers continues to rise, leading to the phenomenon of labor migration. This research aims to analyze the patterns of remittance utilization by Indonesian Migrant Workers' (IMW) families from Jago Village, Central Lombok Regency. In this study, a quantitative descriptive research method was employed, and the analytical tool applied was percentage analysis to calculate the usage of remittances by IMW families in their home village. Primary data were obtained through questionnaires, interviews, and observations conducted on IMW families in Jago Village, Central Lombok Regency. The research findings indicate that the majority of remittance utilization by migrant families is dominated by consumption-oriented purposes. Approximately 70.5 percent of the respondents exhibited a pattern of using remittances for consumptive purposes, while 29.5 percent of the respondents used remittances for productive purposes.